Nasal inoculation of the commensal Neisseria lactamica inhibits carriage of Neisseria meningitidis by young adults: A controlled human infection study. - Deasy, A; Guccione, E; Dale, A; Andrews, N; Evans, C; Bennett, J; Bratcher, H; Maiden, M; Gorringe, A; Read, R (Oxford University Press, 2015)
Background Herd protection by meningococcal vaccines is conferred by population-level reduction of meningococcal nasopharyngeal colonization. Given the inverse epidemiological association between colonization by commensalNeisseria lactamicaand meningococcal disease, we investigated whether controlled infection of human volunteers withN. lactamicaprevents colonization byNeisseria meningitidis. Methods In a block-randomized human challenge study, 310 university students were inoculated with 10^4 colony-forming units ofN. lactamicaor were sham-inoculated, and carriage was monitored for 26 weeks, after which all participants were reinoculated withN. lactamicaand resampled 2 weeks later. Results At baseline, naturalN. meningitidiscarriage in the control group was 22.4% (36/161), which increased to 33.6% (48/143) by week 26. Two weeks after inoculation ofN. lactamica, 33.6% (48/143) of the challenge group became colonized withN. lactamica. In this group, meningococcal carriage reduced from 24.2% (36/149) at inoculation to 14.7% (21/143) 2 weeks after inoculation (−9.5%;P= .006). The inhibition of meningococcal carriage was only observed in carriers ofN. lactamica, was due both to displacement of existing meningococci and to inhibition of new acquisition, and persisted over at least 16 weeks. Crossover inoculation of controls withN. lactamicareplicated the result. Genome sequencing showed that inhibition affected multiple meningococcal sequence types. Results The inhibition of meningococcal carriage byN. lactamicais even more potent than after glycoconjugate meningococcal vaccination.Neisseria lactamicaor its components could be a novel bacterial medicine to suppress meningococcal outbreaks. This observation explains the epidemiological observation of natural immunity conferred by carriage ofN. lactamica.